Only time will tell [compact disc, unabridged] - Archer, Jeffrey, 1940- (Archer, Jeffrey, 1940- Clifton chronicles, 2011)
A dock worker in Bristol, Harry Clifton never knew his father, but he learns about life on the docks from his uncle who expects Harry to join him at the shipyard once he's left school. But then his unexpected gift wins him a scholarship to an exclusive boys' school, and his life will never be the same again.